Formação continuada de docentes do ensino superior: para além dos recursos tecnológicos / Higher Education Teacher Continuing Education: Beyond the Technology Resources - Nunes, Vicente; Giacomo, Antônio (Revista Internacional de Aprendizaje en la Educación Superior, 2016)
ABSTRACT The article deals with the continuing education experience for the use of 8,500 teachers Information and Communication Technologies a private education institution present in all of Brazil with more than 500,000 students. The training was carried out with the purpose of learning based on the authorship with the use of digital resources. The first stage of training was carried out with 60 teachers who have become multipliers and will do the same type of training with teachers in their states. The experience is a success and we already have positive results in various parts of our country. This training also seeks to promote the exchange and sharing of actions in the area of educational technology and for this we use the blog feature to form a virtual community. We believe this training will contribute to creating innovative teaching methods as necessary for the contextualization of our education. RESUMEN O artigo trata da experiência de formação continuada para o uso das Tecnologias de Informação e Comunicação de 8.500 docentes de uma instituição de ensino privada presente em todo o território brasileiro com mais de 500 mil alunos. A formação foi realizada com a proposta de aprendizagem baseada na autoria com o uso de recursos digitais. A primeira etapa da formação foi realizada com 60 docentes que se tornaram multiplicadores e farão o mesmo tipo de formação com os docentes em seus estados. A experiência está sendo bem sucedida e já temos resultados positivos em diversos pontos de nosso país. Essa formação também procura favorecer a troca e compartilhamento de ações na área de tecnologia educacional e para isso usamos o recurso do blog para a formação de uma comunidade virtual. Acreditamos que essa formação vai favorecer o surgimento das inovações pedagógicas tão necessárias para a contextualização de nossa Educação. Contato principal: vwnunes@gmail.com